2020
DOI: 10.1016/j.canep.2020.101720
|View full text |Cite
|
Sign up to set email alerts
|

Impact of geography on Scottish cancer diagnoses in primary care: Results from a national cancer diagnosis audit

Abstract: Main text word count = 3519

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Flytkjær Virgilsen et al report that longer distance to hospital increase the DI for some cancers, especially for those cancers that are more difficult to diagnose (2019). Research from Scotland suggest that rural living does not lead to an increased DI for cancer in general (Murchie, Adam, et al, 2020 ), and rural primary care practitioner initiated diagnostic action within the system just as likely when comparing with their urban counterparts in a European setting (Murchie, Khor, et al, 2020 ). However, Bergin et al ( 2018 ) report that rural living is associated with longer time to diagnosis and treatment for CRC in Australia (Bergin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flytkjær Virgilsen et al report that longer distance to hospital increase the DI for some cancers, especially for those cancers that are more difficult to diagnose (2019). Research from Scotland suggest that rural living does not lead to an increased DI for cancer in general (Murchie, Adam, et al, 2020 ), and rural primary care practitioner initiated diagnostic action within the system just as likely when comparing with their urban counterparts in a European setting (Murchie, Khor, et al, 2020 ). However, Bergin et al ( 2018 ) report that rural living is associated with longer time to diagnosis and treatment for CRC in Australia (Bergin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long travel distance and travel time for patients to diagnostic facilities in secondary care might influence the possibility for and willingness of patients to attend these procedures. A Scottish study has reported that rural patients diagnosed with cancer were more likely to have had blood tests ordered by their GPs [ 15 ]. Possibly, primary care physicians working at the most remote primary care centres could be more inclined to request FITs as a part of their clinical investigation before decision on referral.…”
Section: Introductionmentioning
confidence: 99%